1997
DOI: 10.2466/pms.1997.84.3c.1411
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting and Feedback for the Development of Instructional Strategies

Abstract: This study was done to evaluate the effectiveness of three practice methods, (a) feedback as knowledge of performance (KP), (b) feedback as knowledge of results combined with the goal-setting method, and (c) a combination of knowledge of performance and results with the goal-setting method on the performance and learning of basketball skills of different complexity. Three groups (n = 26) of children followed the practice methods and the performance (result), and technique of simple and complex basketball skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Tzetzis et al. 29 ) showed that, for learning a physical skill, goal setting and feedback are among the most important factors. However, they suggested that, feedback does not improve performance when feedback is separated from goals.…”
Section: Discussionmentioning
confidence: 99%
“…Tzetzis et al. 29 ) showed that, for learning a physical skill, goal setting and feedback are among the most important factors. However, they suggested that, feedback does not improve performance when feedback is separated from goals.…”
Section: Discussionmentioning
confidence: 99%
“…Die Gruppe mit dem normativ-negativen Feedback konnte allerdings gegenüber der normativ-positiven Gruppe weitere Leistungssteigerungen erreichen. Möglicherweise funktioniert der zusätzlich präsentierte Referenzwert hier als Zielstellungsinstruktion (Goal-Setting; Tzetzis et al 1997) und fördert die Motivation und die Zuversicht, weitere Leistungssteigerungen zu erzielen.…”
Section: Ergänzende Rückmeldungenunclassified
“…In the early middle years, as children are just beginning to compare their performance with those of their peers, involvement in competitive sports should be minimal (1,14,24,33). It is more important to work on the perceptual motor skills, decision-making skills, and problem-solving skills necessary for participation in a number of different sports rather than prematurely specializing in one or two sports (14,30,57).…”
Section: Middle Childhoodmentioning
confidence: 99%